Recepcja idei postmodernizmu w pedagogice radykalnej Petera McLarena - Kruszelnicki, Wojciech (Chowanna, 2020)
The aim of this paper is to comprehensively reconstruct the reception of postmodernism in Peter McLaren’s critical/radical pedagogy. On a more general level, the article discusses the pedagogical perils of uncritical infatuation with poststructuralist and postmodernist principles of dismantling grand metanarratives and debunking the notions of truth, totality, and universalism and replacing them with the notions of pluralism and perspectivism. The author seeks to verify the statement that McLaren’s response to postmodern developments in philosophy and social theory is in as much similar to that of Henry Giroux’s that it produces a project of education informed by postmodern ideas. The thesis – advanced in the mid 1990s by Tomasz Szkudlarek – is refuted on the basis of thorough a analysis of both earlier and more contemporary texts of McLaren where the main tenets of postmodern theory are severely criticized. The argument about the evolution of McLaren’s thought from a cautious appropriation of some elements of postmodernism to its downright condemnation is supported by the theory of its increasing radicalization under the influence of Marxism. The alternative to the illusory radicality of postmodernism – denounced as affirming the status-quo – is “pedagogy of revolution,” which emerges as strictly political, interventionist praxis whose aim is no longer discourse analysis but concrete social struggle against the oppressive capitalist class relations.